Supplementation with fortified lipid-based and blended complementary foods has variable impact on body composition among Rural Bangladeshi children: A cluster-randomized controlled trial - Shaikh, Saijuddin; Campbell, Rebecca K; Mehra, Sucheta; Kabir, Alamgir; Schulze, Kerry J; Wu, Lee; Ali, Hasmot; Shamim, Abu Ahmed; West, Keith P; Christian, Parul (Oxford Academic, 2022)
This article was published in the Journal of Nutrition by Oxford Academic [ Copyright C The Author(s) on behalf of the American Society for Nutrition 2020. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/),] and the definite version is available at: https://doi.org/10.1093/jn/nxaa061 The Journal's website is at: https://academic.oup.com/jn/article/150/7/1924/5815134